1995
DOI: 10.1172/jci117706
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 enhances ventricular hypertrophy and function during the onset of experimental cardiac failure.

Abstract: To determine whether additional hypertrophy would be beneficial or maladaptive in cardiac failure, the effects of insulin-like growth factor (IGF-1) were investigated in rats with left ventricular (LV) dysfunction. In normal rats, 3 mg/kg per d of recombinant human IGF-1 for 14 d augmented LV wt (32%) and increased LV/body wt ratio (P < 0.01). 2 d after coronary occlusion, rats were randomized to IGF-1 (3 mg/kg per d) or placebo. After 2 wk, IGF-1-treated rats showed significant increases in LV wt (13%) and LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(185 citation statements)
references
References 55 publications
6
171
0
3
Order By: Relevance
“…This has some similarity to the physiological response to IGF-I seen in experimental animal models. Mice with experimental heart failure treated with IGF-I showed no induction of cardiac hypertrophy at baseline plasma levels of IGF-I (mean 229 ng\ml) but hypertrophy associated with an increase in cardiac output was seen at higher plasma IGF-I levels (mean 601 ng\ml) [38]. Importantly, normal myoblasts treated with media collected from IGF-I-secreting cells also showed a hypertrophic response, demonstrating the paracrine hypertrophic effects of IGF-I.…”
Section: Discussionmentioning
confidence: 93%
“…This has some similarity to the physiological response to IGF-I seen in experimental animal models. Mice with experimental heart failure treated with IGF-I showed no induction of cardiac hypertrophy at baseline plasma levels of IGF-I (mean 229 ng\ml) but hypertrophy associated with an increase in cardiac output was seen at higher plasma IGF-I levels (mean 601 ng\ml) [38]. Importantly, normal myoblasts treated with media collected from IGF-I-secreting cells also showed a hypertrophic response, demonstrating the paracrine hypertrophic effects of IGF-I.…”
Section: Discussionmentioning
confidence: 93%
“…Duerr et al (10) suggested that the increase in the heart weight of rats administered IGF1 for 2 weeks was caused mainly by myocyte hypertrophy. However, in transgenic mice expressing IGF1 specifically in the heart, an increase in myocyte number was reported (12).…”
Section: Overexpression Of Igf1r Induced Compensatedmentioning
confidence: 99%
“…Pathway in the Heart-There is growing evidence to suggest that pathological and physiological cardiac hypertrophy are mediated by distinct signaling pathways (10,16,21,(33)(34)(35)(36)(37)(38)(39)(40). It is therefore likely that the transcriptional regulation of pathological and physiological hypertrophy will also be different.…”
Section: Transcriptional Effects Induced By the Igf1r-pi3k(p110␣)mentioning
confidence: 99%
See 1 more Smart Citation
“…The IGF system has been implicated in the pathogenesis of hypertension [7], atheromatous vascular disease [8,9], cardiomegaly [10], ischaemic disease [11] and cardiac failure [12,13]. IGF bioactivity is modulated by a series of specific high-affinity IGFBPs [14].…”
Section: Introductionmentioning
confidence: 99%